CEO duality, board size and firm performance : Evidence in Vietnam - Le, Hanh Thi My; Ting, Irene Wei Kiong; Kweh, Qian Long; Ngo, Ha Lam Tan (Inderscience Publishers, 2023)
From the perspective of the agency and stewardship theories for explaining the relationship between corporate governance and firm performance, this study examines the impacts of CEO duality and board size on the firm performance. We assess the association between CEO duality, board size and firm performance of top 200 companies listed on the Vietnam Stock Exchange (VSE) over 2014–2015. Our findings show that: 1) CEO duality limits the monitoring function of the board, and a large board size promotes dominance and power of leaders that create more conflicts; 2) the number of executive directors in the top management positively influences firm performance. Findings of our study certainly help policymakers and other stakeholders understand the relationship between CEO duality, board size and firm performance. Overall, this study highlights the CEO duality and the relationship of board size and firm performance in a nation with less protection of minority shareholders.